2017
DOI: 10.1371/journal.pone.0175370
|View full text |Cite
|
Sign up to set email alerts
|

Association between fibromyalgia syndrome and peptic ulcer disease development

Abstract: PurposeThe correlation of fibromyalgia syndrome (FMS) with peptic ulcer disease (PUD) is unclear. We therefore conducted a cohort study to investigate whether FMS is correlated with an increased risk of PUD.MethodsIn this study, we established an FMS cohort comprising 26068 patients aged more than 20 years who were diagnosed with FMS from 2000 to 2011. Furthermore, we established a control cohort by randomly choosing 104269 people without FMS who were matched to the FMS patients by gender, age, and index year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…The reason why our finding is inconsistent with others’ might be that we used clinical diagnostic criteria whereas others used questionnaires such as the Hospital Anxiety and Depression Score or the Beck Depression Inventory to identify depression. The observed incidence of depression in our study was also lower than those reported by other studies in Taiwan, which the prevalence of depression ranged from 3.35% to 6.0%3335 in FM patients and ranged from 1.05% to 2.27% in the general population 36. The reason might be that we did not include dysthymia (ICD-9-CM 300.4) (Appendix 1, Supplemental Digital Content 1, http://links.lww.com/CJP/A585) whereas those studies included dysthymia as a diagnostic code to identify depression.…”
Section: Discussioncontrasting
confidence: 83%
“…The reason why our finding is inconsistent with others’ might be that we used clinical diagnostic criteria whereas others used questionnaires such as the Hospital Anxiety and Depression Score or the Beck Depression Inventory to identify depression. The observed incidence of depression in our study was also lower than those reported by other studies in Taiwan, which the prevalence of depression ranged from 3.35% to 6.0%3335 in FM patients and ranged from 1.05% to 2.27% in the general population 36. The reason might be that we did not include dysthymia (ICD-9-CM 300.4) (Appendix 1, Supplemental Digital Content 1, http://links.lww.com/CJP/A585) whereas those studies included dysthymia as a diagnostic code to identify depression.…”
Section: Discussioncontrasting
confidence: 83%
“…Many medical conditions are more common in people with migraine compared to the general population [33]. There is a small body of literature examining rates of single medical conditions among people with and without migraine, and over the past decade, a growing body of literature has emerged examining the effect of headache day frequency on rates of migraine comorbidities and the effects of selected comorbidities on headache progression [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28]. After adjusting for sociodemographic variables, the cohort with migraine was about three times more likely to report a medical diagnosis of insomnia, depression, anxiety, and gastric ulcer/GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have reported that rates of comorbidities increase by headache day frequency among people with migraine comparing people with EM and CM and/or stratifying by low, moderate and high frequency EM [26,30,31,[37][38][39][40][41]. The existence of the comorbidities that we found with migraine are in general alignment with data reported in the scientific literature, although rates (whether odds ratios or percentages) vary by condition and by study, likely due in some part to methodological and measurement issues as well as differences in the subjects studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations